Circulating endothelial progenitor cells in patients with cardiac syndrome X. Issue 9 (28th December 2006) - Shmilovich, Haim; Deutsch, Varda; Roth, Arie; Miller, Hylton; Keren, Gad; George, Jacob
Abstract : Background: Cardiac syndrome X (CSX) encompasses the constellation of anginal chest pain in the presence of a pathological functional test and a normal coronary angiogram. Endothelial progenitor cells (EPCs) in the peripheral circulation contribute to tissue vascularisation. Objective: To investigate the number and functional properties of circulating EPCs in patients with CSX. Methods: 17 patients with CSX and a referent population (n = 20) were matched for age, atherosclerotic risk factors and use of drugs. Numbers of EPCs were studied by FACS, and their functional properties, including their proliferative capacity, adherence to matrix and mature endothelial cells as well as their ability to support in vitro tube formation, were investigated. Levels of soluble markers that associate with peripheral mobilisation and homing were studied in the serum samples of all subjects. Results: Patients with CSX had significantly increased numbers of circulating EPCs as compared with the referent population (both CD34+/KDR and CD34+/CD133+). The proliferative capacity of EPCs and their ability to support in vitro tube formation were significantly impaired in patients with CSX as compared with the referent population. However, adhesiveness of EPCs from patients with CSX to fibronectin and cultured mature endothelial cells was enhanced as compared with the referent population. Serum vascular endothelial growth factor correlated with peripheral CD34+/KDR cell numbers, whereas serum concentration of erythropoietin correlated with the number of circulating CD34+/CD133+ cells Conclusion: Patients with CSX have a significantly altered circulating EPC phenotype that could potentially aid in understanding the complex pathogenesis of the syndrome.